Moving European research on work and ageing forward: overview and agenda - Schalk, René; Veldhoven, Marc van; Lange, Annet H. de; De Witte, Hans; Kraus, Katrin; Stamov-Roßnagel, Christian; Tordera, Nuria; van der Heijden, Beatrice; Zappalà, Salvatore; Bal, Matthijs; Bertrand, Françoise; Claes, Rita; et al. (European journal of work and organizational psychology, 2010)
This paper summarizes the state of affairs of European research on ageing and work. After a close inspection of the age construct, an overview is presented of research in four areas: the relationship between age and HR-policies, early retirement, age and performance/employability, age and health/well-being. The overview results in a research agenda on work and ageing and in recommendations for practice.
Gesehen am10.08.2023